Emissions of atmospherically reactive gases nitrous acid and nitric oxide from Arctic permafrost peatlands - Bhattarai, Hem Raj; Marushchak, Maija E; Ronkainen, Jussi; Lamprecht, Richard E; Siljanen, Henri M P; Martikainen, Pertti J; Biasi, Christina; Maljanen, Marja
2022